THE EFFECT OF SUGAR CONCENTRATION IN KOMBUCHA, KEJEK TEA AND ASAM KANDIS (Garciniaxanthochymus) ON ANTIOXIDANT ACTIVITY, TOTAL ALCOHOL AND TOTAL ACID - Soni, M.Farm., Dang; Abdillah, Muhammad Nur; Junaedi, Effan Cahyati; Panjaitan, Destrien Resmita (Jurnal Ilmiah Farmako Bahari, 2025)
This study aims to determine the effect of sugar concentration and the addition of asam kandis on antioxidant activity, total alcohol and total acid in kombucha drinks. The test began with a test of the characteristics of the simplicia phytochemical screening. The antioxidant activity was then examined using the DPPH method, the total alcohol content was determined using gas chromatography, and the total acid test was performed using titration. The results of the simplicia characteristic test showed that the simplicia used had met the standards of the Indonesian herbal pharmacopoeia, and the results of the phytochemical screening test showed that only saponins did not show their presence, both kejek tea, asam kandis and a combination of both. The results of the DPPH test showed that the sample with optimal antioxidant activity was in Formula 4 with a percentage inhibition value of 82% ± 0.08, total alcohol of 0.09% ± 0.12 and total acid of 1.57% ± 0.17. This study also proves that the combination of kejek tea, kandis acid and higher sugar content can increase antioxidant activity, total alcohol and total acid, but the total alcohol and total acid are still below the safe limit. Nikmati pengalaman bermain slot, grafis epik dan fitur bonus hadir untuk meningkatkan peluang kemenangan.